Modelling the return of shariah with underlying indices of national stock exchange of India : a case of 3SLS and GMM estimation / Saif Siddiqui and Safika Praveen Sheikh. - Siddiqui, Saif; Sheikh, Safika Praveen (Universiti Teknologi Mara Selangor, 2016)
Shariah indices can be used to construct socially reliable investment products that are attractive for those, who do not wish to invest in undesired business. National Stock Exchange of India introduced Nifty 50 Shariah and Nifty 500 Shariah indices to provide alternative indices for Shariah compliant companies. The study is an attempt to reveal the relationship between Nifty 50 Shariah and Nifty 500 Shariah with their underlying indices, Nifty 50 and Nifty 500.For this purpose a period of 01/01/2007 to 31/12/2015 is taken. Based on various objectives, techniques like Descriptive statistics, Correlation, Co-integration test, 3SLS and GMM estimation are used. It is concluded that return of Shariah Indices are better and risk is lesser, than underlying indices. These indices are the better option for portfolios.